Direct MR arthrography of the shoulder under axial traction: Feasibility study to evaluate the superior labrum‐biceps tendon complex and articular cartilage. Issue 5 (27th September 2012) - Becce, Fabio; Richarme, Delphine; Omoumi, Patrick; Djahangiri, Ali; Farron, Alain; Meuli, Reto; Theumann, Nicolas
Abstract Purpose: To assess the value of adding axial traction to direct MR arthrography of the shoulder, in terms of subacromial and glenohumeral joint space widths, and coverage of the superior labrum‐biceps tendon complex and articular cartilage by contrast material. Materials and Methods: Twenty‐one patients investigated by direct MR arthrography of the shoulder were prospectively included. Studies were performed with a 3 Tesla (T) unit and included a three‐dimensional isotropic fat‐suppressed T1‐weighted gradient‐recalled echo sequence, without and with axial traction (4 kg). Two radiologists independently measured the width of the subacromial, superior, and inferior glenohumeral joint spaces. They subsequently rated the amount of contrast material around the superior labrum‐biceps tendon complex and between glenohumeral cartilage surfaces, using a three‐point scale: 0 = no, 1 = partial, 2 = full. Results: Under traction, the subacromial (Δ = 2.0 mm, P = 0.0003), superior (Δ = 0.7 mm, P = 0.0001) and inferior (Δ = 1.4 mm, P = 0.0006) glenohumeral joint space widths were all significantly increased, and both readers noted significantly more contrast material around the superior labrum‐biceps tendon complex (P = 0.014), and between the superior (P = 0.001) and inferior (P = 0.025) glenohumeral cartilage surfaces. Conclusion: Direct MR arthrography of the shoulder under axial traction increases subacromial and glenohumeral joint space widths, and prompts better coverage of the superior labrum‐biceps tendon complex and articular cartilage by contrast material. J. Magn. Reson. Imaging 2013;37:1228–1233. © 2012 Wiley Periodicals, Inc.